The Realization of Cooperative Principles in BBC Tv Series Sherlock - Selita Siregar (Passage, 2016)
The present study examines the observance and non-observance of the maxims and investigates the perlocutionary effect of Sherlock Holmes’ utterances. The study employs a descriptive qualitative method in analyzing the conversations. The data are in the form of conversations between the characters in Sherlock TV series episode 1 entitled A Study in Pink. Using Grice’s cooperative principle, the study reveals that character Sherlock Holmes is dominantly performing non-observance of the maxims in his utterances. The occurrences of non-observance of the maxims in characters’ utterances are flouting maxim, violating maxim, and opting out of maxim. The study also shows that flouting maxim of quantity and relation are dominantly occurred in Sherlock Holmes’ utterances. By performing floating maxim of quantity and relation, Sherlock Holmes tends to withhold the information. Generating non-observance of the maxims affects to the interlocutors, in other word is the perlocutionary effects. It is found that the types of perlocutionary acts of Sherlock Holmes’ utterances are various. The occurrence of perlocutionary acts are irritating, amazing, annoying, insulting, impressing, distracting, amusing and prompting. In addition, the findings also indicate that the perlocutionary acts occur depending on each character, whether they are always giving positive or negative feedback to Sherlock Holme’s utterances.Keywords: Grice’s cooperative principle, observance of maxims, non-observance of maxims, types of non-observance of the maxims, perlocutionary acts, Sherlock TV series